Application of PD, PI, and PID Control Mode on Vessel Ve203 at Biodiesel Pilot Plant - Mohd Rozi bin Musa, Ahmad Razin Syakireen bin Mohd Rozi (Progress in Engineering Application and Technology, 2023)
This study is to apply the Proportional Derivatives (PD), Proportional Integral (PI) and Proportional Integral Derivatives (PID) control mode on vessel VE203 during heating temperature process. This experiment is to aim to find the suitable parameters to use in DCS system at biodiesel pilot plant in UTHM for doing heating process. Also, this experiment is to find a low overshoot value between process value with setpoint value, and find the best rise time and cycling time. Besides that, redraw the p&id drawing also include in this experiment is to improve the p&id drawing form manufacturing to tally with the actual plant. The method that is apply in this experiment is “trial and error” method. By doing this method is easier to find the suitable parameters by make analysis of each response control mode. The result will compare of each control mode by looking the overshoot value and the rise time. This is because the equipment in biodiesel pilot plant at UTHM are related to the response of the control system. Such as, the quality of steam, the quality of piping, the length of piping, the loss of pressure in fraction loss, the age of temperature valve, the age of temperature transmitter, the surrounding of vessel and size of vessel. After all the data obtain, the result has been finding and it show the best parameters of PID control mode is by set the proportional is 2, integral is 500ms and derivative is 500ms. That parameters combine can get the best result of the overshoot value and rise time which is overshoot value can get 1.1 degree Celsius and the rise time is taking about 4 minutes.